2019
DOI: 10.1093/ajh/hpz039
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Myocardial Perfusion in Different Blood Pressure Phenotypes and Its Association With Arterial Stiffness Indices

Abstract: BACKGROUND We investigated for the first time whether patients with recent-onset, uncomplicated hypertension and different hypertension phenotypes exhibit altered values of subendocardial viability ratio (SEVR), a surrogate measure of myocardial perfusion that correlates with the ratio of subendocardial to subepicardial blood flow. We additionally explored whether SEVR correlates with arterial stiffness in a population free from the long-term effects of essential hypertension. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
3
3
0
2
Order By: Relevance
“…As expected, in our study, we observed a significant negative relation between SEVR and MAP (r = −0.301, p = 0.026), and a borderline negative relation with SBP (r = −0.257, p = 0.058). In line with previous studies, 11 , 20 , 34 our data support the hypothesis that arterial hypertension is strongly related to arterial stiffness and impaired subendocardial perfusion. The underlying mechanism is not completely clarified.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, in our study, we observed a significant negative relation between SEVR and MAP (r = −0.301, p = 0.026), and a borderline negative relation with SBP (r = −0.257, p = 0.058). In line with previous studies, 11 , 20 , 34 our data support the hypothesis that arterial hypertension is strongly related to arterial stiffness and impaired subendocardial perfusion. The underlying mechanism is not completely clarified.…”
Section: Discussionsupporting
confidence: 93%
“… 8 DPTI, which is the area under the diastolic phase in the aortic profile, estimates myocardial oxygen supply, whereas SPTI (the area under the systolic phase) represents cardiac tissue oxygen consumption. 9 As previously described in patients with different hypertension phenotypes, 34 we suggest that SEVR may be considered a valid alternative to invasive assessment of microvascular coronary perfusion. Although, the relative lack of studies comparing SEVR values to other estimations of endocardial perfusion (by other cardiac imaging techniques) represents a possible limitation to the systematic use of SEVR, and further studies are needed.…”
Section: Discussionsupporting
confidence: 60%
“…Anyfanti et al [ 50 ] also emphasize the usefulness of SEVR in assessing microvascular coronary perfusion as well as its variability according to blood pressure phenotype. SEVR varies according to blood pressure phenotype, and the group of investigators observed that normotensive patients have higher SEVR values compared to those with masked hypertension, white-coat hypertension or true hypertension ( p = 0.017).…”
Section: Discussionmentioning
confidence: 99%
“…Arterial hypertension is characterised by diffuse microvascular damage (Fig. 3d, Figure 1, Supplemental Digital Content, http://links.lww.com/HJH/C223) [202][203][204][205][206]. Hypertension and inflammation have a bidirectional physiological and pathophysiological background [207,208].…”
Section: Arterial Hypertensionmentioning
confidence: 99%